The Land Of Complexity 19th and 20th Century Northern Borneo Socio-Demographic History: A Review - Nour Muhammad Adriani; Labibatussolihah Labibatussolihah; Mohammad Refi Omar Ar Razy; Andi Suwirta (Institut Teknologi Sepuluh Nopember, 2021)
North Borneo has always been the object of international interests and politics. This situation is the effect of socio-demographic plurality that led to the absence of a cohesive socio-political identity that can unite them together. This study aims to analyze the social demographic history of the people of North Borneo (Kalimantan) in the 19th and 20th centuries to understand the complex geopolitics in the region during the decolonialisation process in the post-Second World War. Using a literature review, there are some points concluded, first, the Malay Sultanate of Brunei had dominated the political structure of the area that influenced the foundation of the Malay social system in North Borneo for the following centuries. Second, the colonial project of James Brooke changed the social order in North Borneo with the significant presence of non-Malay groups such as the Chinese until the mid-20th century. Third, the Japanese occupation during the Second World War had brought nationalism among the natives. This spirit had led to an attitude of ethnonationalism that makes it was challenging to build a cohesive national identity among different ethnic groups there. Fourth, after the war, regional conflicts due to the Cold War triggered differences in political systems among the new states that gained independence